REPRESENTASI PENGETAHUAN PADA WEB SEMANTIK UNTUK MENINGKATKAN NILAI EFEKTIFITAS PENCARIAN DATA SURAT (STUDI KASUS: PT ANGKASA PURA I CABANG SEPINGGAN BALIKPAPAN ) - Tri Setia Yoga Nugroho; Herlina Jayadianti; Yuli Fauziah (Jurusan Teknik Informatika, 2018)
AbstractPT. Angkasa Pura I branch Sepinggan, Balikpapan still uses the web with a little interactive (browsing or searching for certain information). The system still has some constraints between, the data searched only in accordance with the origin of the sender of the letter. Information gleaned from web searches will make it hard for users to find other broader content, consequently if the search keyword does not match the text contained in the information, the information will not appear. The method used is semantic ontology method, and use protege as ontology design, then use netbean and library Jena as interface design. The methodology used in this final project is the methodology methodology of Guidelines for Rapid APPlication Engineering (GRAPPLE). The GRAPPLE methodology is a simplified framework of the Rapid Application Development (RAD) system development method. GRAPPLE methodology is a system development methodology that each stage consists of several actions, and each action produces a UML diagram. UML is a good modeling language to apply in development. UML has the benefit of providing an overview of systems that are easily understood by developers. UML also makes it easy to translate diagram form into coding. The results obtained in making this application shows that the new application can cover the constraints existing in the previous application, so as to increase the effectiveness of searching a letter. Comparison of test results proved that new applications more minimize the constraints that occur. Keywords: Semantic Web, Ontology, Protege, Letter